Emotional Intelligence, Occupational Stress and Job Performance in the Romanian Banking System: A Case Study Approach - TĂNĂSESCU, Ramona-Ioana; LEON, Ramona-Diana (Management Dynamics in the Knowledge Economy, 2019)
The research aims to analyze the relationships developed among emotional intelligence, occupational stress and employee performance in the financial banking sector. In other words, it aims to: (i) analyze the specialized literature regarding the concepts of emotional intelligence, occupational stress and job performance; (ii) to measure employees’ emotional intelligence, occupational stress and work performance; and (v) to analyze the relationship established among the aforementioned variables (emotional intelligence, occupational stress, job performance). A quantitative approach is adopted and a case study strategy is employed due to the fact that the research focuses on investigating a phenomenon which is frequently encountered in the real context of today’s organizations. Thus, a single-case study analysis is used and a survey based on a questionnaire is developed among 55 employees from the administration department of ING Bank Romania (Bucharest). The hypotheses are tested using partial least square - structural equations modeling and the results prove that in the Romanian banking institutions: (i) there is a negative relationship between employees’ emotional intelligence and the occupational stress; and (ii) there is a positive relationship between emotional intelligence and job performance. These findings have both theoretical and practical implications. At the theoretical level, the present study extends the theory from the human resources management field by proposing a model for evaluating the relationships established among emotional intelligence, occupational stress and job performance in the Romanian banking financial system. At a practical level, it increases managers’ understanding regarding the factors that influence employees’ performance and it provides several strategic directions that could be taken into account for future improvement.